Turkish Validity and Reliability of the Smartphone Overuse Screening Questionnaire - Kuru, Tacettin; Uymaz, Pelin; Cömertoğlu, Seher; Çelenk, Sinem (Addicta: The Turkish Journal on Addictions, 2022)
This study aims to examine Turkish validity and reliability of the Smartphone Overuse Screening Questionnaire. The study group consisted of 400 students enrolled in different departments of a public university. The Smartphone Addiction Scale-Short Version and the Young’s Internet Addiction Test-Short Form were used for criterion validity. For the internal consistency of the scale, the Cronbach’s alpha was calculated. Five items were removed from the questionnaire due to high covariance error in the items loaded into different factors. The new 23-item scale consisted of 6 factors with acceptable goodness-of-fit values. (χ2 /df = 2.83, root mean square error of approximation = 0.06, Comparative Fit Index = 0.90, Goodness of Fit Index = 0.87, Incremental Fit Index = 0.90). For the total score of the scale, the Cronbach’s alpha was 0.93 and test– retest reliability coefficient was .79. (p